Marine Bacterial Diversity in Coastal Sichang Island, the Upper Gulf of Thailand, in 2011 Wet Season - Somboonna, Naraporn; Wilantho, Alisa; Rerngsamran, Panan; Tongsima, Sissades (Frontiers in Marine Science, 2019)
Tha Wang coast in Sichang island, Chonburi province, Thailand, serves a major pier, cargo transportation and is populated with anthropogenic activities. Hence, monitoring of environmental status, in part by microbial diversity, is essential. Previously, the coastal marine microbiota of this area in a dry season (February 2011) had been reported, but the database for a wet season is none. As marine microbiota in several sites were reported fluctuate between dry and wet seasons, specifically in the 2011 that one of the largest flood in Thailand history even occurred from July 2011 to January 2012; the present study thereby first revealed the coastal Sichang water microbiota in the 2011 wet season (July 2011) using metagenomic derived 16S rRNA gene sequencing. Wet and dry seasons showed differences in prokaryotic community richness and evenness: community similarity indices by Jaccard, Lennon, and Yue and Clayton were 2.06–58.28%. This resulted in differences in metabolic potentials, for instances the lower metabolisms for energy and nutrient cycling but the greater in pathogenesis in wet season. Our data were also compared against the flooding water microbiota nearby to Chonburi province to observe any possible correlation; and the coastal Sichang was found distinct given diverse sources of flooding water and local contamination might affect the diversity. In conclusion, this wet-season microbiota supported the better knowledge on the seasonal microbiota of coastal Sichang island.